2012
DOI: 10.1111/j.1365-2036.2012.05055.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: bismuth‐based therapy for Helicobacter pylori eradication in children

Abstract: Background: Because of the decrease in the Helicobacter pylori eradication rate after standard triple therapy with a proton pump inhibitor and two antibiotics, bismuth-based therapy has recently been recommended as alternate firstline regimen in children. Aim: To comprehensively review the clinical, pharmacologic and microbiologic properties of bismuth salts, and to summarise the evidence for the therapeutic efficacy of bismuth-based therapy for H. pylori eradication in children. Methods: Bibliographical searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
4
1
Order By: Relevance
“…Bismuth-based quadruple eradication regimen is highly effective in H. pylori infection but has the disadvantages of risking poor compliance and causing side effects. 36 In contrast to other studies, we did not observe any treatment abandonment. We observed high eradication rates in both groups and decreased complaints of abdominal pain and distention in the B. lactis group on days 7 and 14.…”
Section: Discussioncontrasting
confidence: 99%
“…Bismuth-based quadruple eradication regimen is highly effective in H. pylori infection but has the disadvantages of risking poor compliance and causing side effects. 36 In contrast to other studies, we did not observe any treatment abandonment. We observed high eradication rates in both groups and decreased complaints of abdominal pain and distention in the B. lactis group on days 7 and 14.…”
Section: Discussioncontrasting
confidence: 99%
“…Bismuth (Bi 3+ ) was shown to inactivate HPU by interacting with the cysteine residue of the mobile flap [103] . Due to the bactericidal activity, bismuth compounds have been widely used to treat gastric ulcers associated to H. pylori infection [104] , [105] .…”
Section: Ureases Inhibitorsmentioning
confidence: 99%
“…Combination therapy does not have a superior eradication rate and, therefore, is not recommended when other treatment regimens are available. Bismuth compounds may play two main roles: heavy metals possess antimicrobial properties and interfere with H. pylori attachment when these electron-dense bodies are deposited on the cell surface ( Pacifico et al, 2012 ), and bismuth compounds have a synergistic effect with antibiotics in overcoming multi-antibiotic resistance ( Ko et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eradication rates in areas with high CLA resistance are lower than those in areas with low CLA resistance (Liang et al, 2012). In a study performed in Wenzhou, Zhejiang province, China, when CLA resistance reached 26.12%, the efficacies of triple therapy and bismuth-containing quadruple therapy based on the antibiotic susceptibility test were 67.32% and 68.49%, respectively (Pan et al, 2020). Studies in Vietnam revealed increased resistance to CLA, with rates of 50.9% in 2006 (Le et al, 2022), 84.6% in 2012 (Le et al, 2022), 92.1% in (Van Thieu et al, 2021, and 81% in 2022 (Borka et al, 2023).…”
Section: Antibiotic Resistance In Helicobacter Pylorimentioning
confidence: 99%